Review of the Validity of Ecology Practicum Instructions: An Evaluation Perspective - Zulhendri, Zulhendri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
This study aims to measure the validity of the ecology practicum instructions. This research is categorized as development research. Data collection techniques employed validation testing. The data analysis technique used the percentage technique. The research findings indicate that the average validity test score of the ecology practicum instructions is 73.33%, categorized as valid. These results suggest that the compiled ecology practicum instructions falls under the valid category and does not require revision.